2014
DOI: 10.4049/jimmunol.1302911
|View full text |Cite
|
Sign up to set email alerts
|

Relapsing–Remitting Central Nervous System Autoimmunity Mediated by GFAP-Specific CD8 T Cells

Abstract: Multiple Sclerosis (MS) is an inflammatory disease of the CNS that causes the demyelination of nerve cells and destroys oligodendrocytes, neurons and axons. Historically, MS has been thought to be a CD4 T cell-mediated autoimmune disease of CNS white matter. However, recent studies have identified CD8 T cell infiltrates and gray matter lesions in MS patients. These findings suggest that CD8 T cells, and CNS antigens other than myelin proteins may be involved during the MS disease process. Here we show that CD8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 87 publications
1
76
1
Order By: Relevance
“…This autoimmune astrocytopathy is probably mediated by antigen-specific cytotoxic T cells [1, 4]. Cytotoxic T cells specific for GFAP-derived peptides were shown to be pathogenic in a mouse model of autoimmune GFAP meningoencephalomyelitis where GFAP-specific CD8 + cytotoxic T cells caused various forms of central nervous system inflammation [9]. Our current results also demonstrated that a few CD8 + T lymphocytes infiltrated the perivascular space and parenchyma of the brain.…”
Section: Discussionsupporting
confidence: 62%
“…This autoimmune astrocytopathy is probably mediated by antigen-specific cytotoxic T cells [1, 4]. Cytotoxic T cells specific for GFAP-derived peptides were shown to be pathogenic in a mouse model of autoimmune GFAP meningoencephalomyelitis where GFAP-specific CD8 + cytotoxic T cells caused various forms of central nervous system inflammation [9]. Our current results also demonstrated that a few CD8 + T lymphocytes infiltrated the perivascular space and parenchyma of the brain.…”
Section: Discussionsupporting
confidence: 62%
“…Oligoclonal CD8 + T cells are overrepresented in MS lesions (15, 16), and myelin-reactive CD8 + T cells are present in peripheral blood of MS patients (17), outnumbering myelin-reactive CD4 + T cells (18). In animal models, CD8 + T cells reactive against myelin basic protein (MBP) and MOG are encephalitogenic (19), and CD8 + T cells reactive against the glial fibrillary acidic protein (GFAP) were recently shown to mediate relapsing-remitting experimental disease (20). In this context it is interesting that we find increased numbers of CD8 + cells among CD3 + CD20 dim T cells in untreated MS patients compared to healthy control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of CNS-resident CD8 T cells were not associated with the vascular lumen as these cells were largely found extravasated beyond the vascular lumen into many parenchymal regions across the CNS. CD8 T cell-astrocyte interactions have also received growing attention (60, 66). Functional evidence that CD8 T cells are prime candidates for a role in CNS immune surveillance is based on the exquisitely specific destruction of transgenic astrocytes expressing MHCI-restricted hemagglutinin (67).…”
Section: Discussionmentioning
confidence: 99%